Kuliah Kerja Nyata UMNU Kebumen Desa Kebutuhduwur (Pendidikan Berbasis Merdeka Belajar) - Sumantri, Riyan Jaya; Mudayat, Mudayat; Lutfiyani, Anisa; Utami, Efrilia Tri Wahyu; Khasani, Muhammad Fahrul; Ningsih, Sri Priyanti; Luqiyarrohman, Luqiyarrohman; Imaroh, Nofi Umu; Annam, Mas Nakhul; Irvan, Muhamad; Alfian, Dien Dinar; Romadhon, Uji (Abdibaraya, 2024)
Real Work Lectures (KKN) are a concrete manifestation of the duties of lecturers and students in implementing the Tri Dharma of Higher Education, namely the service aspect. KKN Group 18 Ma'arif Nahdlatul Ulama University Kebumen also focuses on educational activities in the community, the aim of which is to improve the quality of human work in the Kebutuhduwur community, so that they become stronger in their personal freedom. The method we use is observation to find out what will be done during the KKN program. Then the results of his observations were to make an educational presentation in Kebutuhduwur Village. Therefore, other activities help the community to develop. In the Kebutuhduwur village community, resources need to be increased because most people lack education, this has an impact on the quality of human activities. Considering that a country's progress can be seen from its current young generation, it is important to instill the importance of education from an early age. In conclusion, there is a need to increase education in the Kebutuhduwur community to improve the quality of its infrastructure. When the quality of natural resources is good, human resources will soon follow.